A Simplified Scoring System for Diagnosing Allergic Rhinitis in Indonesian Primary Care Settings: A Cross-Sectional Study Comparing Accuracy to Specialist Diagnosis - Febria Suryani; Irna Nettles; Aisyah Andina Rasyid; Fifia Ardinanti (Sriwijaya Journal of Otorhinolaryngology, 2025)
Introduction: Allergic rhinitis (AR) is a prevalent condition in Indonesia, yet often underdiagnosed and undertreated in primary care settings. Access to specialist otorhinolaryngologists is limited, particularly in rural areas. A simplified, accurate diagnostic tool for primary care physicians (PCPs) could significantly improve early diagnosis and management. This study aimed to develop and validate a simplified scoring system for AR diagnosis in Indonesian primary care, comparing its accuracy to the gold standard of specialist diagnosis. Methods: A cross-sectional study was conducted in five major Indonesian cities (Medan, Palembang, Jakarta, Surabaya, and Makassar) across various primary care clinics. Patients presenting with nasal symptoms suggestive of AR were recruited. Each patient was assessed by a PCP using the newly developed "Indonesian Allergic Rhinitis Score" (IARS) and subsequently by a board-certified otorhinolaryngologist. The IARS included key symptoms and history elements weighted based on existing literature and expert consensus. The otorhinolaryngologist's diagnosis, based on a comprehensive history, physical examination (including nasal endoscopy when indicated), and allergy testing (skin prick test or specific IgE), served as the reference standard. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and1 area under the receiver operating characteristic curve (AUC)2 were calculated to evaluate the IARS's diagnostic accuracy. Results: A total of 1500 patients were included in the study (300 from each city). The mean age was 32.4 years (SD = 10.2), with a slight female predominance (58%). The IARS demonstrated a sensitivity of 85.3% (95% CI: 83.1-87.3%), specificity of 79.6% (95% CI: 76.8-82.2%), PPV of 82.5% (95% CI: 80.2-84.6%), and NPV of 83.0% (95% CI: 80.3-85.4%) for diagnosing AR. The AUC was 0.89 (95% CI: 0.87-0.91), indicating good diagnostic accuracy. The most common symptoms reported were nasal congestion (92%), rhinorrhea (88%), sneezing (85%), and itchy nose (79%). Conclusion: The IARS provides a simple, accurate, and readily implementable tool for diagnosing AR in Indonesian primary care settings. Its high sensitivity and acceptable specificity suggest it can effectively identify individuals who require further evaluation and management for AR, improving access to care and potentially reducing the burden of undiagnosed allergic disease.